Instructional Game Strategies in Education: A Meta-Analysis of Gamification and Game-Based Learning on Student Engagement, Motivation, and Academic Achievement - Radhiani, Ahyani; Farouk Abouseada; Wildan; Kameliani (International Journal of Learning Reformation in Elementary Education, 2026)
This study aims to explore the effects of gamification and game-based learning on learners’ behavior, which includes academic performance, involvement, and motivation. It also analyzes the efficacy and prevalence of gamification as well as gaming-oriented learning research across diverse educational stages, regions, and scientific fields. This meta-analysis consists of 60 selected articles published between 2013 and 2023 on Scopus, ERIC, and the Web of Science, that have passed the screening process and met the predetermined criteria. Findings show that gamification generates bigger influence on learners’ engagement (0.65 [0.43, 0.87]), while game-based learning has more impact on motivation (0.46 [0.28, 0.64]) and achievement (1.09 [0.60, 1.59]). Results also indicate that the effectiveness of gamification and game-based learning is more prevalent at the university level, in South Asian countries, and in the humanities. On the contrary, research on these learning methods is more popular at the university level, in East Asian countries, and within the sciences field.